Ways to improve mechanisms for providing agricultural production with technical means - Fayzieva Shirin; Djurayev Bekzod; Samiyeva Gulnoza (E3S Web of Conferences)
The scientific work reflects the ways of improving the mechanisms for providing agricultural production with technical means. The article scientifically substantiates that losses during harvesting of agricultural crops amount to about 3 percent of the total harvest. The article calculates the prospective change in the volume of agricultural machinery by analyzing the level of acquisition of new machinery by peasant (farming) households, and these calculations are expressed in formulas. The work divides the forecasting of agricultural machinery modernization processes into 3 main groups and performs a conditionally multifactor regression analysis. The study recommends that when purchasing agricultural machinery, first of all, a correct assessment of the financial condition of manufacturers is carried out. The article presents an analysis of the dependence of peasant farms on technical modernization and proposes a multifactor regression method for carrying out calculations.